The Influence of Dancing Activities on Women's Self-Image - Adrianna Banio (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2018)
Dancing not only improves our development, but also changes us. It changes our attitude to many issues. It influences our temperament thus transforming the perception of our body. The chief aim of this research was to prove that dancing classes are a form of work on reaching self-awareness and that they have therapeutic properties. The subjects were female participants of all kinds of dancing classes, conducted in various schools by different instructors. 51 females, aged 20 - 60 years old voluntarily participated in a diagnostic survey. Dancing class participants, often unknowingly, undergo a certain metamorphosis. Indisputably, dancing has therapeutic influence; it allows to create and discover hitherto unknown recesses of ourselves. Dancing classes considerably diminish our low self-esteem and distorted perception of our body. The analysis of research shows that behavior of women who participated in dancing class change so that they can more effectively fulfill their life aims.